2004
DOI: 10.1210/en.2003-0792
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits Paclitaxel-Induced Apoptosis via the Phosphorylation of Apoptosis Signal-Regulating Kinase 1 in Human Ovarian Cancer Cell Lines

Abstract: The influence of postoperative estrogen replacement therapy on the sensitivity of ovarian cancer to paclitaxel remains elusive. We examined whether estrogen affects paclitaxel-induced apoptosis in the Caov-3 human ovarian cancer cell line, which expresses estrogen receptor. 17beta-Estradiol (E2) significantly reversed the paclitaxel-induced apoptosis and reduction of cell viability, and a highly selective estrogen receptor antagonist, ICI182,780, and a phosphatidylinositol 3-kinase inhibitor, LY294002, attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…We therefore propose that Nox4-dependent cell survival signaling is mediated by the AKT-ASK1 kinase cascade, and that antagonizing this signaling pathway by DPI or siNox4RNAs results in activation of apoptosis. Similarly, the anticancer drug paclitaxelinduced apoptosis of ovarian cancer cells is mediated by negative regulation of AKT-ASK1 phosphorylation signaling (Mabuchi et al, 2004) and AKT activation by H 2 O 2 confers protection against apoptosis (Wang et al, 2000). It has been reported that ROS oxidize thioredoxin (TRX), a negative regulator of ASK1, and thereby dissociate TRX from pre-existing TRX-ASK1 complexes, resulting in the activation of ASK1 and the subsequent ASK1-dependent apoptosis (Saitoh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose that Nox4-dependent cell survival signaling is mediated by the AKT-ASK1 kinase cascade, and that antagonizing this signaling pathway by DPI or siNox4RNAs results in activation of apoptosis. Similarly, the anticancer drug paclitaxelinduced apoptosis of ovarian cancer cells is mediated by negative regulation of AKT-ASK1 phosphorylation signaling (Mabuchi et al, 2004) and AKT activation by H 2 O 2 confers protection against apoptosis (Wang et al, 2000). It has been reported that ROS oxidize thioredoxin (TRX), a negative regulator of ASK1, and thereby dissociate TRX from pre-existing TRX-ASK1 complexes, resulting in the activation of ASK1 and the subsequent ASK1-dependent apoptosis (Saitoh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(Anand et al 2003, Yang et al 2006. Also known is that estrogen protects breast and ovarian cancer cells from taxol-induced apoptosis (Mabuchi et al 2004, Sui et al 2007. Based on our data that Aurora-A downregulation can override E 2 -induced growth and transformation, we speculated that downregulation of Aurora-A might counteract the estrogen-mediated decrease in Doc sensitivity as well.…”
Section: Aurora-a Knockdown Overrides Estrogenmediated Decrease In Domentioning
confidence: 80%
“…Alternatively, in addition to being pro-proliferative, estrogen has been shown to be a survival factor also. Estrogen has been shown to abrogate the apoptotic response of ovarian cancer cells to paclitaxel (Mabuchi et al 2004) and ER-positive breast cancer cells tend to be more resistant to anti-neoplastic drugs such as paclitaxel and Doc (Sui et al 2007). On the other hand, Aurora-A has been emerging as on anti-cancer target for reasons related to its role in cell cycle regulation, checkpoint evasion, centrosome amplification, and aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments have yielded inconsistent results regarding the estrogen stimulation of cancer cell proliferation. Certain in vitro experiments have shown that estrogen is capable of stimulating the proliferation of malignant cells (12,13), whereas results of other studies showed tumor cell growth inhibition by estrogen (14), and yet other authors found no effect of estrogen on malignant cell growth (15,16). Furthermore, current scientific evidence does not show HRT to adversely affect outcome in patients following treatment for ovarian malignancy (6,16).…”
Section: Introductionmentioning
confidence: 99%